Black carbon pollution in China from 2001 to 2019: Patterns, trends, and drivers. (1st May 2023) - He, Chao; Niu, Xiaoxiao; Ye, Zhixiang; Wu, Qian; Liu, Lijun; Zhao, Yue; Ni, Jinmian; Li, Bin; Jin, Jiming
Abstract: Based on a near real–time 10 km × 10 km resolution black carbon (BC) concentration dataset, this study investigated the spatial patterns, trend variations, and drivers of BC concentrations in China from 2001 to 2019 with spatial analysis, trend analysis, hotspot clustering, and multiscale geographically weighted regression (MGWR). The results indicate that Beijing–Tianjin–Hebei, the Chengdu–Chongqing agglomeration, Pearl River Delta, and East China Plain were the hotspot centers of BC concentration in China. From 2001 to 2019, the average rate of decline in BC concentrations across China was 0.36 μg/m 3 /year ( p < 0.001), with BC concentrations peaking around 2006 and sustaining a decline for the next decade or so. The rate of BC decline was higher in Central, North, and East China than in other regions. The MGWR model revealed the spatial heterogeneity of the influences of different drivers. A number of enterprises had significant effects on BC in East, North, and Southwest China; coal production had strong effects on BC in Southwest and East China; electricity consumption had better effects on BC in Northeast, Northwest, and East China than in other regions; the ratio of secondary industries had the greatest effects on BC in North and Southwest China; and CO2 emissions had the strongest effects on BC in East and North China. Meanwhile, the reduction of BC emissions from the industrial sector was the dominant factor in the decrease of BC concentration in China. These findings provide references and policy prescriptions for how cities in different regions can reduce BC emissions. Graphical abstract: Image 1 Highlights: The regions of high BC concentration in China are located east of the Hu line. The BC decreased at a rate of 0.36 μg/m 3 ( p < 0.001) per year from 2001 to 2019 in China. Multiscale geographically weighted regression indicated a spatial heterogeneity in driving factors. The pronounced decrease in BC emissions is the dominant contributor to the falling BC concentrations.